Influences of Dual Air-Swirler Angles on Swirling Injection and Combustion of Kerosene-Air at a Supercritical Pressure - Danyang Wang; Danyang Wang; Dongxin Huang; Jianguo Xu; Hua Meng; Hua Meng (Aerospace Research Communications)
High-pressure swirling injection and combustion are important phenomena in a modern gas turbine engine as its compression ratio has been significantly increased to improve thermodynamic efficiency. Large eddy simulations are conducted to analyze turbulent flow and combustion of kerosene-air in a dual-air-swirler gas turbine model combustor at a supercritical pressure of 4 MPa, above the critical pressure of kerosene. The present work focuses particularly on effects of the two air swirler angles on flow and combustion dynamics. Numerical results indicate that the inner air swirler exerts strong impact on fuel-air mixing and chemical reactions inside the inner injector, leading to a Y shaped recirculating flow and a V shaped flame at an inner swirler angle of 40°. The precessing vortex core (PVC) is generated by the inner air swirling injection, and detailed analyses reveal that the PVC frequency is controlled mainly by the inner swirl number and the maximum axial velocity from the inner injector. The outer air swirler makes significant impact on the central recirculation structure and turbulent combustion inside the combustion chamber and weakly influences the PVC frequency. For the present supercritical-pressure turbulent combustion in a dual-air-swirler system, it appears that proper combination of the two air swirler angles could avoid chemical reactions deep inside the injector while enhancing fuel-air mixing and combustion in the combustion chamber.